2000
DOI: 10.1126/science.287.5456.1265
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic Loss and Inclusion Body Formation in α-Synuclein Mice: Implications for Neurodegenerative Disorders

Abstract: To elucidate the role of the synaptic protein alpha-synuclein in neurodegenerative disorders, transgenic mice expressing wild-type human alpha-synuclein were generated. Neuronal expression of human alpha-synuclein resulted in progressive accumulation of alpha-synuclein-and ubiquitin-immunoreactive inclusions in neurons in the neocortex, hippocampus, and substantia nigra. Ultrastructural analysis revealed both electron-dense intranuclear deposits and cytoplasmic inclusions. These alterations were associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
1,316
2
18

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,677 publications
(1,383 citation statements)
references
References 25 publications
47
1,316
2
18
Order By: Relevance
“…It is highly expressed in presynaptic neurons and although its normal function is not known, it is speculated to be involved with transport. Overexpression of a-synuclein in a transgenic organism resulted in a parkinsonian-like phenotype (Masliah et al 2000) as well as mutated forms found in early onset Parkinson's disease in humans (Kruger et al 1998;Polymeropoulos et al 1997), suggesting that abnormal expression/function contributes to the neurodegenerativeprocess. Mutated forms of a-synuclein were found to affect membrane binding and association to brain vesicles (Jensen et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is highly expressed in presynaptic neurons and although its normal function is not known, it is speculated to be involved with transport. Overexpression of a-synuclein in a transgenic organism resulted in a parkinsonian-like phenotype (Masliah et al 2000) as well as mutated forms found in early onset Parkinson's disease in humans (Kruger et al 1998;Polymeropoulos et al 1997), suggesting that abnormal expression/function contributes to the neurodegenerativeprocess. Mutated forms of a-synuclein were found to affect membrane binding and association to brain vesicles (Jensen et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, the phosphorylation of serine-129 has been shown to promote fibril formation, a particular form of aggregation, and often thought to be associated with disease . All mouse models of overexpressed a-synuclein (Masliah et al 2000;van der Putten et al 2000) and in vitro studies with wild-type and early-onset Parkinson's disease mutant a-synuclein produce non-fibrillar oligomers (Conway et al 2000). However, the Drosophila model of a-synuclein did produce fibrils (Feany and Bender 2000).…”
Section: Discussionmentioning
confidence: 99%
“…1) were developed in the laboratory of Eliezer Masliah at UCSD [21] and were designated "line 61" to differentiate them from a previously published line driven by the PDGF promoter (line D: [22]). The 2 lines markedly differ in the pattern of alpha-synuclein over-expression and level [21,23].…”
Section: General Descriptionmentioning
confidence: 99%
“…This model was selected because mice from this line develop ha-synuclein immunoreactive inclusions distributed through the neocortex and hippocampus similar to what has been described in DLB. [46][47][48] A total of 48 ha-synuclein tg mice from line D (12 months old) were injected with 3 ml of the lentiviral preparations (1.5 Â 10 7 TU) into the temporal cortex and hippocampus. Briefly, as previously described, 45 mice were placed under anesthesia on a Koft stereotaxic apparatus and coordinates (AP -1.5 mm, lateral 1 mm, depth 2 mm) were determined as per the Franklin and Paxinos Atlas.…”
Section: Transgenic Mouse Lines and Intracerebral Injections Of Lentimentioning
confidence: 99%